2015
DOI: 10.4049/jimmunol.1500957
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of B Lymphopoiesis by Adipocytes and IL-1–Producing Myeloid-Derived Suppressor Cells

Abstract: B-lymphopoiesis declines with age, and this decline not only correlates with increased adipose tissue in the bone marrow (BM), but also adipocyte-derived factors are known to inhibit B-lymphopoiesis. Using co-cultures of mouse BM cells with OP9 stromal cells, we found that adipocyte-conditioned medium (ACM) induces the generation of CD11b+Gr1+ myeloid cells which inhibit B-cell development in vitro. ACM-induced CD11b+Gr1+ cells express Arg1 (arginase) and Nos2 (iNos), and suppress CD4+ T-cell proliferation, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 78 publications
6
75
0
Order By: Relevance
“…In the mouse retrovirus immunodeficiency system, ex vivo derived M-MDSCs from LP-BM5-infected mice also induced a moderate expansion of Tregs in vitro, but concurrently suppressed their IL-10 production (114 (44,162). More recent study showed that MDSCs in the bone marrow of aged mice suppressed B cell lymphopoiesis in an IL-1-dependent manner (74,75). B cells play crucial roles in cancer as sources of malignant cells in several lymphomas (136) and as sources of tumor-specific antibodies (144).…”
Section: Cd4mentioning
confidence: 99%
“…In the mouse retrovirus immunodeficiency system, ex vivo derived M-MDSCs from LP-BM5-infected mice also induced a moderate expansion of Tregs in vitro, but concurrently suppressed their IL-10 production (114 (44,162). More recent study showed that MDSCs in the bone marrow of aged mice suppressed B cell lymphopoiesis in an IL-1-dependent manner (74,75). B cells play crucial roles in cancer as sources of malignant cells in several lymphomas (136) and as sources of tumor-specific antibodies (144).…”
Section: Cd4mentioning
confidence: 99%
“…B lymphopoiesis cultures of rabbit BM cells and OP9 stromal cells were performed in the presence of adipocyte-conditioned medium (ACM), and they found that the production of CD79a + B lineage cells was greatly inhibited, suggesting that adipocytes produce factors that negatively regulate B lymphopoiesis. In similar cultures of progenitors from human and mouse BM, ACM also inhibited B lymphopoiesis (Bilwani and Knight, 2012, Kennedy and Knight, 2015). In fact, the inhibitory activity of ACM appears to be conserved between mammals, as we found human, mouse, and rabbit B lymphopoiesis were all inhibited by ACM generated from adipocytes of these species interchangeably.…”
Section: Age-related Changes To the Bm Microenvironmentmentioning
confidence: 90%
“…MDSCs are most known for their capacity to inhibit T cell responses (Gabrilovich and Nagaraj, 2009), while only few studies have explored their interactions with other cell types (Green et al, 2013, Green et al, 2015, Kennedy and Knight, 2015, O’Connor et al, 2015, Zhu et al, 2007). Because the identification of MDSCs as suppressors of B lymphopoiesis is novel, we became intrigued by how this might be occurring.…”
Section: Age-related Changes To the Bm Microenvironmentmentioning
confidence: 99%
“…Our laboratory discovered that these M-MDSCs also strongly inhibited B cell proliferation (7) and B regulatory cell IL-10 responses (11); to our knowledge, this is the first report of MDSC-mediated suppression of B cells. Subsequently, additional evidence for B cells as targets of MDSCs has been presented (12)(13)(14), particularly in autoimmunity (15)(16)(17)(18) and during B cell lymphopoiesis (19)(20)(21). There is increasing appreciation of the role MDSCs play in viral systems (22).…”
Section: Introductionmentioning
confidence: 99%